Rehabilitation of Bamboos in Kaimur and Vindhyan Region, U.P. - Lal, Shyam (Indian Forester, 1995)
The study area occupied hills and plateau, poor and shallow soils, adverse moisture conditions. Therefore plantation of Dalbergia sissoo, Acacia catechu, Tectona grandis, Emblica officinalis, Azadirachta indica and Terminalia bellirica, are not economically feasible. Naturally, bamboo appeared a suitable species for this area. Their distribution and management is given in detail.